2014
DOI: 10.1016/j.celrep.2014.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Toll-like Receptor-2 by Endogenous Matrix Metalloproteinase-2 Modulates Dendritic-Cell-Mediated Inflammatory Responses

Abstract: SUMMARY Matrix metalloproteinase-2 (MMP-2) is involved in several physiological mechanisms, including wound healing and tumor progression. We show that MMP-2 directly stimulates dendritic cells (DCs) to both up-regulate OX40L on the cell surface and secrete inflammatory cytokines. The mechanism underlying DC activation includes physical association with Toll-like receptor-2 (TLR2), leading to NF-κB activation, OX40L up-regulation on DCs and ensuing TH2 differentiation. Significantly, MMP-2 polarizes T cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 65 publications
2
33
0
4
Order By: Relevance
“…MMP2 modulates many physiological conditions including wound repair and tissue remodeling (22). In physiological condition, MMP2 is expressed by periodontal ligament cells (23) and acts in response to infection, tissue remodeling and injury.…”
Section: Discussionmentioning
confidence: 99%
“…MMP2 modulates many physiological conditions including wound repair and tissue remodeling (22). In physiological condition, MMP2 is expressed by periodontal ligament cells (23) and acts in response to infection, tissue remodeling and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of serum cytokines revealed a distinct inflammatory signature (TNF-α and IL-6) only in sera obtained from WT mice where as the sera from knockout mice had no inflammatory cytokines. Similarly, WT and tlr2 − / − mice adoptively transferred with OT-II cells and injected with OVA + MMP-2 revealed T H 2 polarization upon re-stimulation only in WT-derived T cells and not in tlr2 − / − cells [15]. Taken together, these studies indicate that MMP-2 primes DCs to skew the adaptive immune response toward a pro-tumorigenic T H 2 phenotype through multiple mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, OX40L-mediated T H 2 differentiation was reversed by introduction of exogenous IL-12, indicating that the mechanism of DC-mediated T cell differentiation is amenable to manipulation by pharmacological intervention [1214]. We found that apart from directly inhibiting IL-12 and consequent T H 1 polarization, exogenous MMP-2 also enhanced T H 2-polarization by upregulating OX40L expression on DCs [11, 15]. It is interesting to note that while only active MMP-2 could degrade IFNAR1 and thus inhibit IL-12 secretion, both active and inactive forms of MMP-2 were able to enhance OX40L expression and stimulate secretion of inflammatory cytokines via the canonical NFκB pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, matrix metalloproteinase-2 (MMP-2) produced by the tumor cells has been linked to promoting TH2 response by acting directly as an antigen, increased OX40L expression and DCs receptor alteration. [55] Tumor cells also develop perforin and granzyme inhibitors to resist CD8+ T-cell and NK cell-induced cytotoxicity. [56] Various other molecules are also involved (discussed elsewhere in this article) which may ultimately lead to immune evasion by tumor cells.…”
Section: Cancer Immunologymentioning
confidence: 99%